2018
DOI: 10.1073/pnas.1722023115
|View full text |Cite
|
Sign up to set email alerts
|

Declining mental health among disadvantaged Americans

Abstract: SignificanceIn the past few years, references to the opioid epidemic, drug poisonings, and associated feelings of despair among Americans, primarily working-class whites, have flooded the media, and related patterns of mortality have been of increasing interest to social scientists. Yet, despite recurring references to distress or despair in journalistic accounts and academic studies, there has been little analysis of whether psychological health among American adults has worsened over the past two decades. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 34 publications
3
72
0
Order By: Relevance
“…We find a similar pattern for alcohol abuse: linear decline in alcohol abuse with age in the mid-1990s has been replaced with a more bi-model distribution across age by the early 2010s. Comparing the prevalence of substance abuse between the 2 periods, the biggest differences are among youngest respondents and those in midlife (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). Figure 2 presents a similar plot by relative SES.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We find a similar pattern for alcohol abuse: linear decline in alcohol abuse with age in the mid-1990s has been replaced with a more bi-model distribution across age by the early 2010s. Comparing the prevalence of substance abuse between the 2 periods, the biggest differences are among youngest respondents and those in midlife (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69). Figure 2 presents a similar plot by relative SES.…”
Section: Discussionmentioning
confidence: 99%
“…We find that differences in the prevalence of drug abuse between the mid-1990s and early-2010s vary by age and by SES. We are not aware of any prior comparisons of trends in drug abuse by age or SES, but Jalal et al 51 observed a bi-modal distribution in unintentional drug overdose trends, with bigger rises in mortality at young ages (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and in later life (50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60). Our results for drug abuse show a similar pattern at older ages, but little period difference at younger ages, except perhaps below age 30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these countries, central and local governments often cannot cover basic social needs, which could affect the quality of life and have an impact on environmental factors that influence child health and growth (Joel et al, ; Kopacova et al, ; Sekiyama, Roosita, & Ohtsuka, ). For example, lower socioeconomic status, income, and education have been associated with higher cardiovascular risk (Jenkins & Ofstedal, ; Winkleby, Jatulis, & Fortmann, ) and mental health problems (Goldman, Glei, & Weinstein, ). Adult height is thus an important longitudinal marker for tracking cumulative net nutrition and population health (Perkins et al, ; Sekiyama et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is comprised of two national surveys conducted in 1995–6 and 2011–14. Goldman, Glei and Weinstein () found a decline in psychological health between the earlier and later MIDUS survey samples for white non‐Hispanics as a whole. Counter to Lamont’s hypothesis, however, they found that the decline was steeper among individuals with lower socioeconomic status (SES): when they compared low‐SES whites in the two surveys, they found significant declines in several indicators of psychological health; yet when they compared high‐SES whites in the two surveys, they found smaller declines or even increases in psychological health.…”
mentioning
confidence: 99%